Curriculum Evaluation of Maharah Istima’ in Intensive Classes: Harmonizing Lesson Plan and Practice - Erna Herawati Faridatul Mahya; Wahidmurni; Syuhadak (Jurusan Pendidikan Bahasa Arab UIN Kiai Ageng Muhammad Besari onorogo, 2025)
This study evaluates the effectiveness of the Maharah Istima’ curriculum in intensive Arabic language classes by examining the alignment between Semester Learning Plans (RPS) and classroom learning practices. A qualitative descriptive approach was employed, utilizing document analysis, classroom observations, and interviews with instructors and curriculum developers for data collection. The data were analyzed through interactive qualitative analysis, which included data reduction, presentation, and conclusion formulation. The results indicate that while the RPS contained clear objectives, materials, and assessment strategies, their implementation in the classroom frequently deviated due to time constraints, varying student abilities, and a lack of readily available authentic materials. Pedagogical adjustments made by instructors often enhanced student engagement, yet these adjustments were not fully aligned with the curriculum design. This study underscores the necessity for regular curriculum evaluation, enhanced communication between curriculum developers and instructors, and the strengthening of professional training focused on adaptive and contextual teaching. These findings contribute to the advancement of Arabic language curricula in higher education, particularly in enhancing the relevance and effectiveness of intensive listening skills instruction. Abstrak Penelitian ini mengevaluasi efektivitas kurikulum Maharah Istima’ pada kelas intensif bahasa Arab dengan menelaah keselarasan antara Rencana Pembelajaran Semester (RPS) dan praktik pembelajaran di kelas. Penelitian ini menggunakan pendekatan deskriptif kualitatif, di mana data dikumpulkan melalui analisis dokumen, observasi kelas, dan wawancara dengan pengajar serta pengembang kurikulum serta dianalisis dengan analisis interaktif kualitatif yang terdiri dari reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa meskipun RPS telah memuat tujuan, materi, dan strategi penilaian yang jelas, implementasinya di kelas kerap menyimpang akibat keterbatasan waktu, variasi kemampuan mahasiswa, dan minimnya materi autentik yang mudah diakses. Penyesuaian pedagogis yang dilakukan pengajar seringkali meningkatkan keterlibatan mahasiswa, namun belum sepenuhnya sejalan dengan desain kurikulum. Studi ini menegaskan perlunya evaluasi kurikulum secara berkala, komunikasi yang lebih intensif antara pengembang kurikulum dan pengajar, serta penguatan pelatihan profesional berbasis pengajaran adaptif dan kontekstual. Temuan ini berkontribusi pada pengembangan kurikulum bahasa Arab di pendidikan tinggi, khususnya dalam memperkuat relevansi dan efektivitas pembelajaran intensif keterampilan menyimak.